Stress
XIV, 203 p.
Keywords: The collected papers in this volume cover the effects of environmental stress under a biological and energetic model. Examples are taken from fossil and living animal populations, and from outlier human populations and traditional societies. These examples indicate that stress increases energy demands and so reduces reproductive fitness. A wide range of stressful situations also are analyzed under the less stringent conditions experienced by modern human populations, when cultural factors assume importance. These emphasize the interaction between genetic, physiological, psychological and social factors in everyday life and in clinical settings.